Potential Of Kirinyuh Weed (Chromolaena odorata) As A Source Of Green Fertilizer in Two District in Kuantan Singingi Regency - Deno Deno Okalia; Desta Andriani; Nopriadi Nopriadi; Gusti Marlina (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2022)
Kuantan Singingi Regency is dominated by marginal soil with the order of soil. The use of Ultisol for the cultivation of problematic plants with poor organic matter and nutrients needs to be overcome by giving organic matter. One of the potential sources of organic fertilizer in Kuantan singingi district is kirinyuh bush (Chromolaena odorata). This study has the objectives of 1) knowing the contribution of biomass and the distribution of kirinyuh. and 2) To determine the potential of kirinyuh as a source of organic fertilizer through the C, N, P and K nutrients it contains. This research is a field research that will be carried out using a survey method with purposive sampling. Kirinyuh's observation locations were in two sub-districts in Kuantan Singingi Regency, namely Kuantan Hulu Kuantan District and Mudik Kuantan Singingi Regency. The results of this study can be concluded that kirinyuh is widely available and easy to obtain in Kuantan singingi Regency and contains high nutrients so that it is very potential to be used as a source of organic fertilizer in the form of green manure. Kirinyuh weed in Kuantan singingi has not been utilized and is often found living in groups on the outskirts of land, roads, rice fields, shrubs and irrigation. Kirinyuh biomass as a source of organic matter varies, generally every 1m2 produces about 2-3 kg of biomass. The results of laboratory analysis, kirinyuh leaves contain nutrients of 42.95% C-organic, 4.41 %N, 1.032 %P and 3.05%K, while the stem contains 45.68% C-Organic.